Interfacial interactions in PMMA/silica nanocomposites enhance the performance of parts created by Fused Filament Fabrication. (21st November 2018) - Street, Dayton P.; Mah, Adeline Huizhen; Patterson, Steven; Pickel, Deanna L.; Bergman, James A.; Stein, Gila E.; Messman, Jamie M.; Kilbey, S. Michael
Abstract: As an additive manufacturing method, Fused Filament Fabrication (FFF) is conceptually attractive due to its agility and adaptability. However, FFF-printed parts exhibit poor mechanical properties as compared to parts manufactured by traditional methods. Here, the addition of silica nanoparticles (Si NPs) into FFF-printed parts is demonstrated to markedly improve a variety of thermomechanical properties. Specifically, dynamic mechanical analysis (DMA) and tensile tests indicate that the glass transition temperature, Young's modulus, elongation at break, ultimate tensile strength, and storage and loss moduli all increase with the Si NP loading. Small-angle X-ray scattering (SAXS) and scanning electron microscopy (SEM) demonstrate similar hierarchical structures in all FFF-printed nanocomposites, which suggests that improvements in material properties with Si NP loading are likely due to an increasing number of hydrogen bonding interactions between PMMA matrix chains and hydroxyl groups on the Si NP surface. The potential of nanocomposite filaments to increase the thermomechanical properties of FFF-printed specimens provides a facile route to overcome limitations in FFF-printed part strength by combining the properties of hard and soft matter. Graphical abstract: Highlights: Si NPs reinforce PMMA parts printed by Fused Filament Fabrication. Thermomechanical properties increase with Si NP loading level. Nanocomposite structure and average size not impacted by Si NP loading level. Favorable polymer-nanoparticle interfacial interactions drive property improvements.